The Icelandic news media in times of crisis and change - Jóhannsdóttir, Valgerður; Ólafsson, Jón Gunnar (Stjórnsýslustofnun, 2018)
The news media around the world has experienced drastic changes in recent decades, and the Icelandic media is no exception. These changes originate in political, economic and not least technological developments. In this article we map key developments in the Icelandic media system and illustrate the changes it has undergone in the first decades of the 21st century. Journalism and media studies are under-researched fields of study in Iceland, and the country is usually absent from comparative work in these fields. Often it is simply grouped together with the other four Nordic countries. We argue that the Icelandic media system differs from those countries in several ways. Whilst it has moved towards the liberal model there are also indications of increased partisanship in the media in the last decade. The smallness of the media system has made it more vulnerable to the increasing competition and commercialisation in the digital era, and Iceland was particularly badly hit by the financial crisis in 2008. News media companies in Iceland are struggling financially, several media outlets have come and gone, mergers have been frequent and trust in the media is low. The view that some sort of public support is required to secure an independent media and high-quality journalism is gaining ground in Iceland. This could lead to its media system becoming more similar to the democratic corporatist Nordic countries than is the case now.